IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN MOVER SCHOOLS (A CASE STUDY AT UPT SD NEGERI KEDUNGBANTENG 02 BAKUNG DISTRICT BLITAR REGENCY) - Wildan Irwahyudi; Ahmad Khoiri; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2023)
The purpose of this study was to identify and obtain information about the implementation of the independent curriculum in mover schools. The method used in this research is a descriptive qualitative method, which describes the subject the situation, and the data obtained during observations and questions so that it becomes useful information and is easily understood by readers. This study explains and provides an overview of the implementation of the independent curriculum in driving schools. The results of this study indicate that the implementation of the curriculum in the driving sc hool has been carried out optimally and is ongoing, although in practice there are still many drawbacks and obstacles. The key to the success of implementing the curriculum in driving schools is that the principal and teachers must have the will to make changes. The principal as a leader must be able to change the mindset of the Human Resources in the school to want to make changes so that the independent curriculum can be applied.